Economic analysis of the fishery activities of Bergobindapur baor at Chaugachha upazila under Jessore district of Bangladesh - Sharif, BM Newaz; Ali, Md Yousuf; Saha, Manos Kumar; Ahmad, Md Anam; Islam, Md Aminur; Amin, Md Ruhul (Asian Journal of Medical and Biological Research, 2016)
The study was conducted on Bergobindapur baor at Chaugachha upazila under Jessore district. The study period was February to June, 2015. Data were collected by using participatory rural appraisal (PRA) tools and personal observation. Net return was loss in 2013-2014 and the loss amount was BDT 254200. Cost benefit-ratio in 2013-2014 was 0.99. Major income (83.30%) of the fishermen community was drawn from the fishery activities of Bergobindapur baor. In 2014-2015, average income of fishermen was BDT 25250 during the fishing period. Within the household of fishermen community, the expenditure for food was 19%, clothing, 3%, childrens education, 19%, medical, 3%, dowry and religion, 33%, agriculture, 13% and others, such as business, accommodation, sanitation etc. 10%, which came from baor activities. The findings of this study indicated that Bergobindapur baor plays a vital role for the support of livelihood of fishermen and net profit from baor was not satisfactory. A long-term strategy should be developed to make the baor profitable. The developed strategic plans should be initiated immediately for the profitability of the baor as well as improving the livelihood conditions of the fishermen engaged with the boar fishery activities. Asian J. Med. Biol. Res. September 2016, 2(3): 436-441